THE VALUES OF MORAL EDUCATION IN THE NOVEL BUNDA CINTA STORY 2 KODI BY ASMA NADIA - Marianti; Kaspullah; Suriadi (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
The focus of this research is what values of moral education are contained in the novel Bunda Kisah Cinta 2 Kodi by Asma Nadia and how is the relevance of moral education in the novel Bunda Kisah Cinta 2 Kodi by Asma Nadia in madrasah/elementary schools. The aim of this research is to describe and analyze the values of moral education in the novel Cinta 2 Kodi by Asma Nadia. To describe the relevance of moral education in the novel